A rare case of Balo's disease in a young adult: A clinical presentation and management - Mansi Singh; Abeer Almusleh; Geethika Mandru; Snigdh Sahu; Ogbonnaya Akuma; Chinaza Mercy Akuma; Brinda Desai; Archit Kumar Nigam; F. N. U. Sandhiya; Manjeet Singh; Aadil Mahmood Khan (Clinical Case Reports, 2024)
Key Clinical Message Accurate diagnosis of rare neurological conditions like Balo's concentric sclerosis (BCS) is challenging but crucial for tailored treatment. Interdisciplinary collaboration and further research are essential to advance our understanding. Abstract This case report presents a 32‐year‐old female patient with a puzzling neurological condition characterized by feverish feelings, joint pain, unclear speech, and an unsteady gait. Initial management did not lead to improvement, and further examination revealed neurological involvement and joint tenderness without signs of inflammatory arthritis. Laboratory investigations ruled out infectious and autoimmune causes. Magnetic resonance imaging (MRI) showed well‐defined lesions with concentric rings, leading to a diagnosis of Balo' concentric sclerosis. Treatment with intravenous methylprednisolone resulted in limited improvement. This case highlights the importance of thorough evaluation and collaboration in diagnosing rare neurological conditions. Further research is needed to enhance the understanding and treatment of rare neurological disorders.